Transporte eletrônico em phased arrays de nanofitas de grafeno - Araújo, Francisco Ronan (2017)
Graphene, a layer of carbon atoms arranged in a honeycomb crystal lattice, has remarkable physical properties. After its experimental obtaining in 2004 by A. K. Geim and K. S. Novoselov, several researches were carried out aiming to understand such physical properties and several possibilities of applications were proposed. At the low energy limit, there is a linearity relationship between energy and momentum for the electric charge carriers in this material and, therefore, they behave as relativistic particles of zero mass, described by the Dirac equation. One of the implications is that the electron-associated eigenfunctions that cross a potential barrier may not undergo damping under certain circumstances, a phenomenon known as Klein's paradox. Even without damping, these eigenfunctions acquire a phase factors that may depend only on the height and width values of the potential barrier. In this study, we investigate the properties transport in two electronic devices that use this phenomenon and that may be associated to phased arrays (electronic systems that have several emitters of waves, mechanically or electromagnetic, properly organized). We studied the electronic transport mechanisms in these physical systems and performed numerical simulations of electrical conductance as a function of energy and electrical conductance as a function of the electric potential and it was observed that the direction of propagation of the electrons can be controlled by varying the values of height and width of potential barriers.